The game-changing impact of POLE mutations in oncology—a review from a gynecologic oncology perspective - Kögl, Johanna; Pan, Teresa L.; Marth, Christian; Zeimet, Alain G. (Frontiers in Oncology, 2024)
Somatic mutations within the exonuclease proofreading domain (EDM) of the DNA polymerase Pol ϵ (POLE) gene are increasingly being discovered in ovarian, colorectal, urological, and, especially, endometrial carcinoma (EC), where these are found in up to 10% of the cases. In EC, there are five confirmed pathogenic somatic POLE-EDM mutations that are located at codons 286, 411, 297, 456, and 459, and these are called “hotspot” mutations. POLE mutant tumors are ultramutated entities with a frequency of base substitution mutations that is among the highest in human tumors. Interestingly, these mutations are associated with excellent clinical outcome in EC. An additional six “non-hotspot” POLE-EDM EC mutations are also considered pathogenic, and they also confer a favorable prognosis. Currently, de-escalation of adjuvant treatment is recommended for patients with EC with stage I–II tumors involving any of these 11 EDM mutations, even in patients with other clinicopathological risk factors. The high tumor mutational burden and the consequent increased infiltration of immune cells due to the overexpression of different neoantigens are probably responsible for the improved prognosis. Ongoing studies are examining POLE hotspot mutations among many non-gynecologic tumors, although the impact of such mutations on clinical outcomes is still a topic of debate. Therapeutic modalities for these hypermutated tumors are also an important consideration, including the need for or de-escalation of adjuvant treatments and the response to immune therapy. This review addresses the critical role of POLE mutations in gynecologic oncology and oncology in general, focusing on definitions, variants, underlying pathogenic mechanisms, upcoming developments in the field, and the clinic behavior associated with such mutations.